Insecurity and neighborhood protection mechanisms in the urban Peru - Bonilla Rojas, Diana; Vizcarra Castillo, Sofía (FLACSO - Sede Ecuador, 2016)
This paper explores and compares, through the use of qualitative techniques, the new perceptions of insecurity generated over the last years among the neighbors of two urban neighborhoods in Peru and the respective neighborhood protection mechanisms implemented in response. On the one hand, the Ronda Urbana of the Agua de Pajaritos neighborhood in Huamachuco district, La Libertad department, and on the other hand, the security grilles and watchmen of the La Huerta neighborhood, in Rimac district, Lima department. While both neighborhoods take place in different urban environments, in both cases we find common characteristics that allow us to approach to eh insecurity perceptions and the visions about security provision, sometimes contradictory to the ideal about civic coexistent in modern cities.